Politics and the Urban Frontier: Transformation and Divergence in Late Urbanizing East Africa - Tom Goodfellow (Oxford University Press, 2022)
Despite the rise of global technocratic ideals of city-making, cities around the world are not merging into indistinguishable duplicates of one another. In fact, as the world urbanizes, urban formations remain diverse in their socio-economic and spatial characteristics, with varying potential to foster economic development and social justice. This book argues that these differences are primarily rooted in politics, and if we continue to view cities as economic and technological projects to be managed rather than terrains of political bargaining and contestation, the quest for better urban futures is doomed to fail. Dominant critical approaches to urban development tend to explain difference with reference to the variegated impacts of neoliberal regulatory institutions. This, however, neglects the multiple ways in which the wider politics of capital accumulation and distribution drive divergent forms of transformation in different urban places. In order to unpack the politics that shapes differential urban development, this book focuses on East Africa as the global urban frontier: the least urbanized but fastest urbanizing region in the world. Drawing on a decade of research spanning three case-study countries (Ethiopia, Rwanda, and Uganda), Politics and the Urban Frontier provides the first sustained, book-length comparative analysis of urban development trajectories in Eastern Africa and the political dynamics underpinning them. Through a focus on infrastructure investment, urban propertyscapes, street-level trading economies, and urban political protest, it offers a multi-scalar, historically grounded, and interdisciplinary analysis of the urban transformations unfolding in the world's most dynamic crucible of urban change.
Keywords: 330; urban development; East Africa; comparative urban politics; late urbanization; infrastructure; planning; protest; Ethiopia; Rwanda; Uganda